2020
DOI: 10.1175/jas-d-19-0227.1
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convective Adjustment of Temperature and Moisture

Abstract: Simple process models and complex climate models are remarkably sensitive to the time scale of convective adjustment τ, but this parameter remains poorly constrained and understood. This study uses the linear-range slope of a semiempirical relationship between precipitation and a lower-free-tropospheric buoyancy measure BL. The BL measure is a function of layer-averaged moist enthalpy in the boundary layer (150-hPa-thick layer above surface), and temperature and moisture in the lower free troposphere (boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 118 publications
0
22
0
Order By: Relevance
“…The CCKW-associated precipitation in this DYNAMO case features a nearly monotonic relationship with saturation fraction, while a hysteresis-like behavior occurs with DCIN and surface fluxes ( Figure 11); the implication is that saturation fraction is the primary driver of precipitation intensity. This conclusion is also supported within the framework of Ahmed et al (2020), in which the lower tropospheric plume buoyancy ( ) is represented as (their Eq. 7):…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The CCKW-associated precipitation in this DYNAMO case features a nearly monotonic relationship with saturation fraction, while a hysteresis-like behavior occurs with DCIN and surface fluxes ( Figure 11); the implication is that saturation fraction is the primary driver of precipitation intensity. This conclusion is also supported within the framework of Ahmed et al (2020), in which the lower tropospheric plume buoyancy ( ) is represented as (their Eq. 7):…”
Section: Discussionmentioning
confidence: 52%
“…For and Π, the subscripts and indicate averages over the boundary layer (1000-850-hPa) and the lower-free-tropospheric layers (850-500-hPa), respectively. and are determined following Ahmed et al (2020). Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 in Adames and Ming 2018b). In the tropics, the main source of diabatic heating is deep cumulus convection, whose buoyancy is sensitive to the thermodynamic environment rather than the large-scale ascent (Brown and Zhang 1997;Mapes 2000;Ahmed and Neelin 2018). Adames and Ming (2018b) showed that anomalous precipitation in simulated MLPSs is more closely in phase with anomalous water vapor, rather than large-scale lifting (their Fig.…”
Section: B Convective Parameterizationmentioning
confidence: 99%
“…The role water vapor plays in modulating the occurrence and organization of tropical deep convection is well documented. For example, a humid free troposphere reduces the dilution that updrafts experience as they ascend (Kuo et al 2017;Ahmed and Neelin 2018). The central role moisture has in tropical convection has led to the hypothesis that waves may exist where water vapor plays a central role in their dynamics (Sobel et al 2001).…”
Section: Introductionmentioning
confidence: 99%